CLINICAL AND BIOCHEMICAL PREDICTORS OF DIABETES MELLITUS MANIFESTATION AFTER MYOCARDIAL INFARCTION - O. L. Barbarash; O. V. Gruzdeva; O. E. Akbasheva; E. I. Palicheva; E. G. Uchasova; V. N. Karetnikova; T. S. Fedorova (Российский кардиологический журнал)
Aim. To identify the most informative parameters of carbohydrate and lipid metabolism which predict the manifestation of type 2 diabetes mellitus (DM-2) within one year after myocardial infarction (MI).Material and methods. The study included 200 MI patients who underwent the assessment of glucose and insulin levels, insulin resistance (IR) index, and lipid profile at Days 1 and 12. The incidence of new DM-2 cases which manifested within a year after MI was assessed.Results. After one year after MI, incident DM-2 was diagnosed in 14,5% of the patients. It was associated with concomitant cardiovascular risk factors, adverse clinical course of acute and longer-term MI periods, and lipid metabolism disturbances. A higher risk of incident DM-2 after MI was linked to IR and an elevation in free fatty acid (FFA) levels (9,5 times or higher) during the acute MI phase.Research Institute for Complex Cardiovascular Disease Issues, Siberian Branch, Russian Academy of Medical Sciences, Kemerovo; 2Kemerovo State Medical Academy, Kemerovo; 3Siberian State Medical University, Tomsk, Russia.